Good governance and conflict resolution in Africa - Silima, T. (My University, 2016)
This article provides an analytical argument about good governance and conflict resolution in Africa. The article aims to explore and explain governance as an act of governing and an applicable practice in Africa. The article is conceptual in nature and it critically engages the application of good governance principles which need to be applied in African countries. The article supports the notion that good governance is characterised by respect for human rights and creating democratic institutions for promoting good governance and conflict resolution in Africa.The article concludes that the focus of government function has now changed, and thefore government and therefore gorvenments in Africa have to comply to true governance model.
Published in: Journal of Public Administration and Development Alternatives. Vol. 1, No.1 , July 2016, 1-14
Keywords: Good governance; Human rights; Conflict resolution